DIFFERENCES OF SOLID STUDENTS MATHEMATICAL PROBLEMS THROUGH RESOURCE BASED LEARNING APPROACH AND REALISTIC MATHEMATICS APPROACH ON MATERIAL SYSTEM EQUAL LINEAR TWO VARIABLES IN CLASS VIII SMP PRIVATE MUHAMMADIYAH 2 MEDAN - Reyni Juliani .; Edy Surya . (KARISMATIKA: Kumpulan Artikel Ilmiah, Informatika, Statistik, Matematika dan Aplikasi, 2021)
This study aims to determine whether there are differences in problem solving skills of mathematics students through a resource-based learning approach with a realistic approach mathematics on the material system of linear equations two variables in class VIII SMP Swasta Muhammadiyah. The population in this study is all students of class VIII SMP Swasta Muhammadiyah 2 Medan consists of 3 classes. From 3 class, two classes were chosen in class VIII-B as experiment class I with RBL approach and class VIII-C as experiment class II with RM approach which amounted to 30 students. This research includes the kind of quasi-experimental research. The instrument used to determine students' mathematical problem solving abilities is a validated problem-solving test in the form of a description. The results showed that from the results of the research given different treatment, the average of the experimental class I with the RBL approach and the experimental class II with RM approach obtained pretest average value of 52.7 and post-test of 78.75 experimental class I while the average value of pretest experiment class II of 47.08 and post-test of 72.17. From the normality test results obtained that the two data derived from the normal distributed population with Lhitung in the experimental class I (RBL) in pretest is 0.1253 and post-test of 0.1268 and in the experimental class II (RM) on pretest is 0, 1204 and the post-test is 0.1315 because Lcount is smaller than Ltable (0.161) then both data are normally distributed. In addition, from homogeneity test results in pretest obtained Fcount is 1.3818 and at post-test obtained 1.2041 smaller than Ftable (1.858) which means that both data have the same variance. After it is known that the data of both classes are normal and homogeneous distribution, then hypothesis testing is done. From result of hypothesis test obtained tcount at pretest is 2,164 and at post-test is 2,099 bigger than ttable (1,671) which mean that H0 is rejected and Ha accepted. Thus it can be concluded that the problem-solving ability of mathematics students taught by approach of learning-based learning differs from the problem solving ability of mathematics students taught with realistic mathematics approach on SPLDV material in class VIII SMP Private Muhammadiyah 2 Medan.